تحديد ثلاثي أسيل غليسرولات (TAGs) في أصناف زيت الزيتون السوري بتقانة الكروماتوغرافيا السائلة عالية الأداء (HPLC) لموسم 1998 (مجلة جامعة اللاذقية - سلسلة العلوم الأساسية, 2018)
أظهرت نتائج تحديد ثلاثي أسيل غليسرولات في أصناف زيت الزيتون السوري: الصوراني، الخضيري، الدعيبلي، الزيتي، القيسي، الدان، تبايناً في نسب الغليسريدات باختلاف الصنف المدروس. فقد لوحظ ارتفاع في نسبة SLO وOLnL بشكل ملحوظ في الزيت القيسي على حساب انخفاض محتواه من التري أوليين (OOO ). وكان التباين في نسبة الغليسريدات الثلاثية( TGs) قليلاً جداً في زيت الزيتون الدعيبلي والخضيري التي تعد من مزروعات المنطقة شبه الرطبة خلال مراحل نضج الثمرة. و من دراسة معاملات الارتباط تبين أن الارتباط بين كمية(OOO) في أصناف زيت الزيتون الصوراني ومراحل نضج الثمرة كان ضعيفاً بينما كانت بقية الأصناف ذات علاقة ارتباط هامة وخاصة في زيت الزيتون دان The results of determining of (TAGs) in Syrian olive oil s varieties such as Sorani, Thouderi, Diapli, Zeiti, Kaisi, and DAN, revealed differences in the rates of these Glycerids according to the different examined variety. It has been noticed that the rate of (SLO) and (OlnL) became higher in Kaisi but lower in Triolein. However the difference in the rate of Triglycerid was very low in Diapli and Khouderi olive oil which are concedered grops of the semi-humid area during the season of fruit s ripeness. Moreover, the results showed that the average of the Triolein (OOO) in the examined varieties of oil, is related to the stages of fruit s ripeness. The study of correlation showed that the relation between the amount of (OOO) in Sorani and the stages of fruit s ripeness was low. However in other varieties these relations were very essential especially in the DAN olive oil.